FLY OVER AND ROAD INTERSECTION - Amruta Laxman Lugade1, Ketaki Bipin Parchandrao2 , Rutuja Kisan Saste 2, Snehal Bhagwat Thorat 2 , Rutuja Sachin Raut 2. (International Journal of Innovations in Engineering Research and Technology, 2022)
Transportation is one of the most important aspect of a developing nation and is necessary for ensuring the growth of urban areas. In India, due to rapid increase in population along with urbanization and improved living condition, the vehicular population have increased massively. Traffic congestions has become a major problem at intersections. The main objective of this project is to analyze traffic problems at a suitable intersection and suggesting an alternate solution. In this study, we have taken three main intersections, two (K.B.P College Chowk) and one (Shetfal Chowk). After analyzing and comparing peak values of 3 intersections, junction with highest peak value is selected. According to IRC: SP: 90-2010, manual for grade separators and elevated structures the maximum volume a rotary can handle is specified as 5000pcu/hr and an elevated structure could be provided beyond this limit. A simple grade separator, that is, a flyover is provided at this intersection to segregate the high volume of traffic. With the flyover bridge at the intersection, a major proportion of the traffic volume could be diverted to the bridges, and time delay can also be reduced over the same period. Thus, the traffic pass at two different levels and leaves no chance for an accident. If this project is implemented, the present and future demands of the traffic flow will be satisfied.